PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE (AI) DALAM PANDANGAN AL-QUR’AN: ANTARA ETIKA DAN EFISIENSI - Rahman, Azibur; Al Ghifari, Fahmul Hikam (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This article explores the integration of Artificial Intelligence (AI) in Islamic education from the perspective of the Qur'an, with a focus on ethics and efficiency. In the digital era, the use of AI has revolutionized learning methods through adaptive systems, virtual tutors, and data-driven dynamic curricula. However, such advancements also raise ethical challenges and potential dehumanization in education, especially within Islamic values that emphasize character and moral development. This study adopts a qualitative library research approach, analyzing relevant Qur’anic verses and contemporary Islamic educational literature. The findings indicate that AI offers significant opportunities to enhance learning efficiency but must be governed by the principles of trust, justice, and maqasid al-shari’ah. The Qur’an provides a firm ethical foundation to respond to technological developments while maintaining spiritual integrity. Therefore, AI-based learning in Islamic education should function as a supportive tool that strengthens the role of educators and fosters learners who are not only intellectually capable but also morally upright.